PERSEPSI NELAYAN PURSE SEINE TERHADAP LAYANAN PELABUHANPERIKANAN SAMUDERA (PPS) BITUNG - Kahimpong, Injly R.; Andaki, Jardie A.; Kotambunan, Olvie V.; Durand, Swenekhe S.; Tambani, Grace O. (AKULTURASI, 2022)
Abstract The Bitung Ocean Fishery Port (PPS) is a Service Technical Implementation Unit (UPT) which in carrying out services to service users is equipped with port facilities. The facilities at PPS Bitung are divided into 3 parts, namely: basic/basic facilities (pier facilities, port pool facilities, navigation equipment facilities, breakwater facilities), functional facilities (TPI facilities, ice factory facilities, refrigeration ice warehouse facilities, marketing building, maintenance room facilities, fleet repair facilities, supply facilities) and supporting facilities (welfare support facilities, administrative support facilities) as well as Bitung PPS administration services. The purpose of this study was to determine whether Purse Seine fishermen know the functions and benefits of the existing facilities and services at Bitung PPS and to determine the Purse Seine fishermen’s perceptions of the existing facilities and services at Bitung PPS. This research method is a survey method. The population in this study was the captain of the Purse Seine ship. The number of samples taken as many as 20 people, using the sampling method. Sampling using incidental sampling method. The data collected in the form of primary data and secondary data. Primary data is data collected directly by researchers, which is done by means of observation and interviews guided by a questionnaire. Secondary data is data collected through a second party, in the form of evidence, records or reports obtained from the Bitung PPS office. Data analysis to determine the knowledge of Purse Seine fishermen using the Guttman scale, while to determine the perceptions of Purse Seine fishermen using a Likert scale. Based on the results of the analysis, it is known that 96.50% of Purse Seine fishermen already know the functions and benefits of the facilities and services provided by PPS Bitung, while 3.50% state that they do not know the functions and benefits of the facilities and services provided by PPS Bitung. This is inseparable from the active role of employees in socializing the functions and benefits of the facilities and services provided by PPS Bitung. Purse Seine fishermen’s perception of all facilities and services provided by PPS Bitung which is assessed based on 4 dimensions is 4.26, which means that fishermen’s perceptions are good about the facilities and services provided by PPS Bitung, there are even some indicators of questions that have very good perceptions of Purse Seine fishermen. Â Keywords: perception; fishermen; PPS Bitung Â Abstrak Pelabuhan Perikanan Samudera (PPS) Bitung merupakan Unit Pelaksanaan Teknis (UPT) Dinas yang dalam melaksanakan pelayanan jasa kepada para pemakai jasa dilengkapi fasilitas pelabuhan. Fasilitas yang berada di PPS Bitung, dibagi menjadi 3 bagian yaitu: Fasilitas pokok/dasar (fasilitas dermaga, fasilitas kolam pelabuhan, fasilitas alat navigasi, fasilitas pemecah gelombang), fasilitas fungsional (fasilitas TPI, fasilitas pabrik es, fasilitas gudang es refrigasi, fasilitas gedung pemasaran, fasilitas ruang pemeliharaan, fasilitas perbaikan armada, fasilitas perbekalan) dan fasilitas penunjang (fasilitas penunjang kesejahteraan, fasilitas penunjang administrasi) berserta layanan administrasi PPS Bitung. Tujuan penelitian ini adalah untuk mengetahui apakah nelayan Purse Seine mengetahui fungsi dan manfaat dari fasilitas dan layanan yang ada di PPS Bitung serta untuk mengetahui persepsi nelayan Purse Seine terhadap fasilitas dan layanan yang ada di PPS Bitung. Metode penelitian ini adalah metode survey. Populasi dalam penelitian ini adalah nahkoda kapal Purse Seine. Jumlah sampel yang di ambil sebanyak 20 orang, dengan menggunakan metode sampling. Pengambilan sample menggunakan metode insidental sampling. Data yang dikumpulkan berupa data primer dan data sekunder. Data primer adalah data yang dikumpulkan langsung oleh peneliti, yang dilakukan dengan cara observasi dan wawancara yang dipandu dengan kuesioner. Data sekunder adalah data yang dikumpulkan melalui pihak kedua, berupa bukti, catatan atau laporan yang diperoleh dari kantor PPS Bitung. Analisis data untuk mengetahui pengetahuan nelayan Purse Seine menggunakan skala Guttman, sedangkan untuk mengetahui persepsi nelayan Purse Seine menggunakan skala Likert. Berdasarkan hasil analisis diketahui bahwa nelayan Purse Seine 96,50% sudah mengetahui fungsi dan manfaat dari fasilitas dan layanan yang disediakan oleh PPS Bitung, sedangkan 3,50% menyatakan tidak mengetahui fungsi dan manfaat dari fasilitas dan layanan yang di sediakan oleh PPS Bitung. Hal ini tidak terlepas dari peran aktif pegawai dalam mensosialisasikan fungsi dan manfaat dari fasilitas dan layanan yang disediakan oleh PPS Bitung. Persepsi nelayan Purse Seine terhadap seluruh fasilitas dan layanan yang disediakan oleh PPS Bitung yang dinilai berdasarkan 4 dimensi diperoleh hasil 4,26 yang berarti persepsi nelayan baik terhadap fasilitas dan layanan yang disediakan oleh PPS Bitung, bahkan ada beberapa indikator pertanyaan yang mempunyai persepsi sangat baik dari nelayan Purse Seine. Â Kata Kunci: persepsi; nelayan; PPS Bitung